Production and characterization of Macronutrient and Zn in Rucah Fish Meatballs with the Addition of Eucheuma cottonii Seaweed - Warsidah, Warsidah (Jurnal Biologi Tropis, 2024)
Trash fish has high nutritional content such as protein, fat and essential minerals, so it has the potential to be used as a processed product for snacks. This research aims to make meatballs from trash fish which are added with Eucheuma cottonii seaweed pulp as a binding agent, to partially substitute the use of wheat flour. This research was carried out by comparing the macronutrient and essential mineral Zn content between trash fish meatballs with the addition of E. cottonii and trash fish using wheat flour alone. The characteristics evaluated include texture and taste, water content, ash content, protein content, fat content and carbohydrate content as well as the essential mineral sen (Zn). The results showed that the addition of Eucheuma cottonii flour significantly improved the texture and taste of trash fish meatballs with an average protein content of 17.55%, average fat of 5.57%, carbohydrates of 14.07% and zinc of 5.6 ppm. Trash fish meatballs without the addition of E. cottonii showed a protein content of 15.15, fat of 5.2%, carbohydrates of 22.09% and zinc of 4.2 ppm.